EFFECTIVE STRATEGIES IN OVERCOMING THE CHALLENGES OF WAKAF MANAGEMENT: A STUDY IN THE LOCAL LEADERSHIP OF MUHAMMADIYAH IN PEKANBARU CITY - Ritonga, Rahmatika (Jurnal Al-Iqtishad, 2025)
Waqf plays a strategic role in the economic and social development of the Muslim community. As one of the instruments of Islamic philanthropy, waqf not only serves as a continuous charitable endowment (amal Jariyah) that provides ongoing rewards for the waqif but also as a productive asset that can enhance societal well-being. This study aims to provide effective strategies for overcoming challenges in waqf management at the Muhammadiyah Regional Leadership in Pekanbaru. This research is a field study employing a descriptive-analytical approach using qualitative methods. Data collection techniques include observation, interviews, and documentation. The findings indicate that effective strategies for addressing waqf management challenges in the Muhammadiyah Regional Leadership of Pekanbaru consist of three main steps. First, public awareness campaigns on waqf to enhance their understanding of its concepts, legal aspects, and benefits. Second, the establishment of professional nazhir to ensure proper and sustainable waqf management. Third, the productive management of waqf assets to generate long-term benefits for the community. Through creative and innovative management, waqf can be developed into businesses, agriculture, or other investments that generate income for society. Collaboration between nazhir, Islamic financial institutions, and the government is essential in supporting more professional waqf management. With these strategies, waqf is expected to become a more effective and sustainable instrument for empowering the Muslim community's economy.